A vendéglátás válasza a gazdasági válságra - Nagy, Imre; Takács, István (Acta Carolus Robertus, 2011)
Since 2006, the catering industry has been experiencing stagnation in circulation, and this process was worsened by the 2009 economic crisis. According to the chairman of the Hungarian Association of the Caterer Corporations, one-third of the industry may disappear completely, which could lead to the end of 40,000 jobs. A really big problem is faced by those larger restaurants that can take in 100-200 people for their happenings, while smaller restaurants can make their business more streamlined in headwind by redundantizing and lowering their costs. Experience has shown that such crises affect luxurious restaurants mostly, because their constant costs are the highest. It is also a serious problem that there is no significant civilian layer in society that could serve as a middle segment for small family restaurants. There are cheap hash-houses, where the price and volume counts, or highly luxurious restaurants. The aim of my thesis is to provide possible solutions for lowering costs and maximizing profit to survive the harsh period with the help of using my own experiences, interviews I made with catering managers and complementing the sources. To shape it into an assessable form I evaluate the catering units considering their location and category. I am looking for those cost-saving methods that would not cause redundancies. Restaurants differ from each other. The environment, the equipment, the personnel management, the consumer demand are different in each case, so the examination of the topic is complex. I hope the thesis manages to provide ideas for the readers, in order to reach more positive outcomes. The study wants to find this way not only by examining the businesses’ inner budget (supplies, pricing, motivating consumption, wages), but also harmonising it with the factors that affect it (the awareness of their errand, marketing tools, inner marketing).